The Mediation of Coloniality in Decolonisation Developments in South African Theological Education - Naidoo, Marilyn ca. 20./21. Jh. (Religions, 2024)
The imperial nature of Christianity structured around colonialism, white supremacy, and apartheid was governed by racially motivated logics that fundamentally define the idea of who could be human. Decades later, the uncomfortable emphasis on decoloniality in South African theological education arises in a contested space despite the need to decentre white, Western methods, interpretations, and experiences. Academic readiness and ownership regarding the implementation of decolonisation initiatives constitute a significant obstacle. They highlight how coloniality mediates and attempts to erase decolonising praxis. This article employs the theoretical framing of Grosfoguel’s analysis of the coloniality of power, of knowledge, and of being, surveys recent educational developments in theological education towards redress to reveal a hesitancy and considers the perspective change of educators towards decolonisation praxis. This article underscores a contextual challenge for the legitimacy of decolonialisation and the need to restore its significance amidst the slow pace of educational transformation in theological education.